EKSISTENSI MGMP IPS DALAM PENGEMBANGAN PROFESIONAL GURU IPS SMP DI KABUPATEN PAMEKASAN - M Abdur Rauf; Amalia Desy Wahyuni; Abdul Muin (LPPM Universitas Kahuripan Kediri, 2026)
This study aims to examine efforts to improve the professionalism of teachers who are members of the MGMP SMP Negeri (Junior High School Teacher Working Group) within the Pamekasan District Education and Culture Office. The research approach uses qualitative methods through interviews, observation, and documentation. The results of the study indicate that teacher involvement in the MGMP program contributes significantly to overall professionalism, not only in pedagogical aspects, but also in mastery of subject matter, ability to develop teaching tools, improved work ethic, and ability to collaborate in learning communities. Various activities such as workshops, structured discussions, and professional mentoring encourage teachers to develop more optimally. These findings confirm that a focused and sustainable MGMP program is an effective strategy in strengthening the professionalism of public junior high school teachers.